2015
DOI: 10.5946/ce.2015.48.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Gastrointestinal Stent Development

Abstract: Endoscopic stenting is increasingly being used in the management of gastrointestinal luminal obstruction, and has become the current treatment of choice for the palliation of blockage caused by malignant or benign growths. A variety of stents have been developed to enhance the efficacy of the procedure, and improvements are ongoing. In this article, we review the history of, and recent advances in, gastrointestinal stenting. We describe the rationale behind the design as well as the resulting outcome for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
0
25
0
3
Order By: Relevance
“…Consequently, plastic stents have rarely been used since the 1990s when uncovered SEMS first became available. SEMS are generally packaged in a compressed form and constrained around a delivery device, making dilation unnecessary and reducing the risks of perforation, obstruction, or migration, which can occur with plastic stents [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, plastic stents have rarely been used since the 1990s when uncovered SEMS first became available. SEMS are generally packaged in a compressed form and constrained around a delivery device, making dilation unnecessary and reducing the risks of perforation, obstruction, or migration, which can occur with plastic stents [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…With FCSEMS, migration is a major problem. Several newly designed stents prevent stent migration; anchoring flaps or flared stent ends are commonly used [ 67 , 68 ]. Studies using FCSEMS with either an anchoring flap or a flared end at the proximal end of the stent reported that the anchoring flap design might be superior in terms of efficacy and a lower migration rate to the flared end [ 69 , 70 ].…”
Section: Novel Stentsmentioning
confidence: 99%
“…Accurate stent positioning, establishing and maintaining luminal patency, and limiting stent migration and adjacent tissue injury are important considerations in the selection and placement of an SEMS. Data on existing SEMSs suggest that stent design can impact clinical success [3-6]. In 2019, the HANAROSTENT® LowAx TM Duodenum (Olympus Corporation of the Americas, Center Valley, PA, USA) was approved by the US Food and Drug Administration (FDA) for palliative treatment of pyloric or duodenal obstructions by malignant neoplasms.…”
Section: Introductionmentioning
confidence: 99%